World cities achieving liveability and vibrancy - Ooi, Giok Ling (World Scientific, 2010)
The book focuses on the major challenges that world cities are facing in such key areas such as governance, social inclusiveness, infrastructural development, financial solvency as well as environmental and ecological sustainability. Based on case studies from cities in North America, Europe, and the Asia-Pacific, top academics, professionals and policymakers from the world over presents their views on how to best strike the balance between growth and sutainability.